Evaluasi Program Perencanaan Persalinan dan Pencegahan Komplikasi (P4K) Sebagai Upaya Menurunkan Angka Kematian Ibu Di Puskesmas Paguyangan Kab. Brebes Tahun 2018 - Khoeroh, Himatul (Jurnal Kesehatan Ilmiah Aufa Royhan, 2019)
Birth Planning and Complications Preventions Program (P4K) was government effort to reduce maternal and new born mortality rate ( AKI ) in Indonesia, but until now Sustainable Development Goals (SDGs) announced globally about 830 woman died every day because complication during pregnancy and childbirth. This research is qualitative study with an early informant determined by purposive sampling. Data collection method through in-depth interviews, observation and documentation 4 early informant consisting of midwives coordinator, village midwives, health cadres and pregnant mothers. One of the triangulation informant is the head of the Family Health Department of Brebes District Health. The results showed on the input element of quality and quantity midwives and cadres as executor is sufficient enough, special funds for P4K program does not exist but the facility of KIA and P4K stickers has met. Process elements showed some part of the program was carried out well with 100% coverage of pregnant women's data and all childbirth was helped by Health care personnel. The village ambulance as a means of transportation was deemed sufficient. However, there was a lack of direct involvement village midwives in filling the sticker column P4K, lack of home visits pregnant women to latching P4K stickers, and Blood donation program for pregnant women has not been carried out. The output element was Primary health care centre of Paguyangan only contributed one case the death of mother in the year 2018.